KURMA MINI BABE (KURSI DAN MEJA MINI BERBAHAN DASAR BAN BEKAS) DENGAN SENI MOTIF ANEKA KARTUN ANAK - Faris Lismana, Hendri Puji; Hadi, Arif Rakhman; Ikhwan, Muhammad Nur (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
The existence of waste tires can cause serious problems for the environment, because it is difficult to decompose waste/ reprocessed difficult. At this time most of the waste tires only used to make the trash, cans, and sandals are not too great economic value. The purpose of this proposal is to make the effort mini-sized tables and chairs are designed using cartoon motif and was made by using waste tires (tangible assets and intangible assets) with a social-based business Technopreneurship. The event was held at the Kingdom Telang Beautiful Sandalwood special Gg Sub Kamal (Pondok Pesantren Al-Kayyis Student west campus of UTM-Bangkalan District), using two systems, namely: (1) system partners with local artisan furniture where students simply provide design , materials and means of production by providing wages, and (2) self-contained system that is student working on his own all production activities. Marketing of the resulting products is done in a straightforward manner to consumers via online (some consumers who order via online pass), door to door campaign to school in kindergarten or early childhood Bangkalan region. In the business activities of this program to get cooperation Babe Mini Dates / Furniture form communities in order to increase market share and network branding or design improvements that increase. Terjadwalkan activity 5 months with the design and realization of cost activity fee of Rp. 9.500.000, - which was approved by the Higher Education.